Evaluation of genetic diversity and relationship among agronomic traits in selected accessions bean collection - Shahin Vaezi; Roghaieh Cheraghafrooz; Ahmad Abbasimoghddam (پژوهش‌های حبوبات ایران)
Genetic diversity in bean collection can be used in breeding program for selection of genotype with desirable agronomic traits. Fifty two accessions of common bean (Phaseolus vulgaris) has been evaluated for genetic diversity of agronomic traits, grain quality and determination of association between grain yield and some morphological traits at Research Farm of National Plant Gene Bank of Iran, Seed and Plant Improvement Institute in Karaj during 2011. Complete randomized block design with two replications has been used for conduction of experiment and statistical analysis. According to Biodiversity International descriptors traits understudy has been recorded. Descriptive statistics results of traits analysis indicated considerable diversity regarding node number on main stem, 100 seed weight, seed number per plant and pod number per plant. Variation for traits of seed number per plant, 100 seed weight, days to maturity and seed yield per plant ranged between 32-150 seeds, 14.8-74.22 g, 46-96 days and 11.2-55.1 g, respectively. Coefficients of variation for genetic and phenotypic were high regarding traits of node number on main stem, pod number per plant, seed number per plant, 100 seed weight and seed yield per plant. All traits except days to flowering (22.3%) and days to forming pod (7.9%) had high heritability between 62.8-82.9%. Based on cluster analysis genotypes understudy classified in tree groups among them two had highest single plant seed yield. Among qualitative characters maximum variation has been observed for pod string and minimum for pod tip curve. According to results of simple correlation, multiple regression and path analysis; pod number per plant, 100 seed weight and seed number per plant as components of yield had the greatest impact on performance of single plant seed yield. During principal component analysis 67.60% of recorded traits variations were due to four factors.